Impact of Induction Therapy on Clinical Outcomes of Kidney Transplant Recipients: A Single-Centre Cohort Study - Vijaya Madhuri Devraj; Gangadhar Taduri; Swarnalatha Guditi; Uttara Das; MP Shamsudheen; Megha Saigal; Raja Kartik Kalidindi (Journal of Renal and Hepatic Disorders, 2023)
The purpose of this study was to evaluate long-term efficacy of immunosuppressive drugs based on the type of induction therapy given to kidney transplant recipients, and determine the occurrence of graft dysfunctions or rejections. We compared the safety and efficacy of anti-thymocyte globulin (ATG) and basiliximab (BAS) in high-risk patients and analyzed the cumulative incidence of immediate, slow, and delayed graft function in kidney transplant recipients to determine their initial short-term graft function. Evaluation of the long-term efficacy after 3 years post-transplantation by assessment of patients and graft survival, incidence of infections, and risks of rejection were the primary endpoints. Patients with stable graft survival were observed more with ATG (85%) than BAS (70%); in contrast, graft dysfunctions, graft nephrectomy, rejection episodes, and patient deaths were more prevalent with BAS than ATG, with statistically significant differences in long-term graft functioning. Patient survival at 3 years in ATG group was 90.4%, compared to 88% in BAS group, and graft survival was 90.4% in the ATG group and 81.3% in the BAS group (P < 0.001). The use of both induction therapies resulted in good patient and graft survival outcomes than placebo, and the results showed that there was a significant difference in both patient and graft survival after 3 years between induction of ATG and BAS, suggesting that ATG can be safer, effective, and preferable drug over BAS for high-risk recipients.